MADRASAH IBTIDAIYAH AL HIDAYAH CK MEDAN POLONIA DISTRICT: 2013 CURRICULUM DEVELOPMENT MANAGEMENT TO INCREASE THE EFFICACY OF LEARNING - Al Farisi, Salman; Neliwati, Neliwati; Daulay, Nurika Khalila (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
This research aims to analyze the management of the 2013 curriculum development in increasing the effectiveness of learning at the Al Hidayah CK Madrasah Ibtidaiyah (MI) Medan Polonia District. This research is a type of qualitative research using a descriptive approach. In gathering this information, the researcher will carry out observations and interviews with the head of the Madrasah, deputy head of the Madrasah for Curriculum, and teachers and other parties concerned with this research. The results of the research concluded that the madrasa head's ability to implement the 2013 curriculum is already running, but the weakness lies in the teachers and parents of the students, because teachers have not thoroughly reflected the 2013 curriculum in the classroom as a result, this has an impact on the effectiveness of learning using the 2013 curriculum. It is difficult to develop the 2013 curriculum. , and in terms of assessment, it is not very effective, where the 2013 curriculum is thematic, the final results of the report cards are per field of study. In conclusion, the madrasa head's policy is not in line with the teacher's wishes, or the teacher does not respond to the policies set by the madrasa head. This has an impact on ineffective coordination between an organization within an educational institution so that the problem of who regulates and who is regulated is unclear, so that it becomes The strength of this research is to understand the direction of the Al Hidayah CK Medan Polonia madrasah